Factors influencing the level of acceptance of group family Takaful amongst primary school staffs in Bukit Beruang, Malacca / Ummu Ajirah Abdul Rauf - Abdul Rauf, Ummu Ajirah (2013)
Takaful or Islamic insurance is part of well growth Islamic finance industry today. The government and the industry player have done many efforts, however the small participation from the society is always doubted. Thus, the variable factors will influence level of acceptance of Group Family Takaful. Due to this problem, Takaful Company should identify which factors that can best fit with level of acceptance of Group Family Takaful amongst primary school staffs in Bukit Beruang, Malacca. The main purpose of this study is to examine and gain a better solution of the significant relationship towards the factors influencing the level of acceptance of Group Family Takaful. There are several factors influencing the level of acceptance of Group Family Takaful, which include agent’s performance, level of knowledge, and advertising. Results of the present study showed that the most influential factors of level of acceptance of Group Family Takaful amongst primary school staffs in Bukit Beruang, Malacca are level of knowledge. At the end of this study, the researcher come out with several recommendations in order to give clear vision for Takaful Company to increase level of acceptance of Group Family Takaful amongst primary school staffs in Bukit Beruang, Malacca.